Dolphin - Rauch, Alan (Animal (Reaktion Books), 2014)
From Flipper to SeaWorld, dolphins have long captured our hearts. We love these friendly, intelligent mammals, and they seem to return our feelings-they enjoy interacting with swimmers and have been known to encircle people under attack by sharks. Despite our familiarity with dolphins, though, we remain ill-informed about how they evolved, how they function, and how they have interacted with humans for millennia. Dolphin dives into the dolphin's zoology, as well as its social and cultural history, to offer a comprehensive view of these delightful creatures.